(untitled) (Jurnal Teknologi (Sciences & Engineering), 2012)
Bagi merealisasikan MOSFET submikron, simpangan cetek ultra berkerintangan rendah diperlukan bagi menghalang kesan saluran pendek dan bagi meningkatkan peranti. Dalam kajian ini, pembentukan simpangan cetek ultra disimulasikan menggunakan perisian ATHENA dan Silvaco Inc. bagi memodelkan resapan dari SOD ke dalam silikon. Simpangan ultra P+N berkualiti tinggi dengan kedalaman 40 nm telah dibentuk menggunakan ciri–ciri yang baik dengan arus bocor serendah 0.5 na/cm2. Simpangan cetek kurang daripada turut diperoleh tetapi kualiti simpangan–simpangan cetek ini kurang baik disebabkan oleh arus bocor permukaan yang tinggi. Pembentukan simpangan dari resapan lapisan polisilikon di atas silikon diikuti oleh SOD di atasnya menghasilkan simpangan yang lebih cetek yang berkerintangan rendah. Kata kunci: Simpangan cetek ultra, resapan, SOD, ATHENA, MOSFET For realizing deep submicron MOSFETs, ultra shallow junctions with low sheet resistance and high doping concentrations are required to suppress short channel effects and to increase the performance. In this paper, ultra shallow junctions were simulated using ATHENA software package from Silvaco TCAD Tools to model the diffusion from spin on dopant (SOD) into silicon. High performance 40 nm P+N shallow junction fabricated by rapid thermal diffusion of B150 into silicon have been obtained. The junction showed very good characteristics with leakage currents as low as 0.5 nA/cm2. Shallow junctions less than 20 nm have also been obtained but the quality was not very good due to very high surface leakage current. Junction formation by diffusion of polysilicon layer on Si substrates then SOD layer deposition on top of it produced shallower junctions with low sheet resistance. Key words: Ultra shallow junction, MOSFET, ULSI, diffusion, spin on dopant, ATHENA, ATLAS